B lymphocyte activation and exhaustion in chronic HIV : novel surrogate markers of generalised immune activation and selective modulation of aberrant B cell responses using vasoactive intestinal peptide (VIP) - Reid, Timothy Dawson (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScMedSc)--Stellenbosch University, 2015.